Geronimo Stilton reporter. 15, Clean sweep - Stilton, Geronimo; Costa, Davide (Stilton, Geronimo. Geronimo Stilton reporter, 2023)
When the owner of the Daily Rat newspaper thinks Thea Stilton, who has vanished without a trace, is responsible for a recent string of robberies in New Mouse City, Geronimo must employ his "famouse" investigative skills to find Thea - and the truth.